2021
DOI: 10.1200/op.20.00890
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity of Cancer Care: An Analysis of Financial Burden in Three Distinct Health Care Systems

Abstract: PURPOSE: The financial toxicity of cancer care is a source of significant distress for patients with cancer. The purpose of this study is to understand factors associated with financial toxicity in three distinct care systems. METHODS: We conducted a cross-sectional survey of patients in three care systems, Stanford Cancer Institute (SCI), VA Palo Alto Health Care System (VAPAHCS), and Santa Clara Valley Medical Center (SCVMC), from October 2017 to May 2019. We assessed demographic factors, employment status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Although it is well established that a cancer diagnosis creates significant financial toxicities for patient and their families [25][26][27] , we found that participants were 3 times more likely to engage in diabetes-related CRN compared with cancer-related CRN. Participants who reported cancer-related CRN reported higher rates of delaying or forgoing not seeing an oncologist due to cost compared with other cancer-related CRN behaviors.…”
Section: Discussioncontrasting
confidence: 61%
“…Although it is well established that a cancer diagnosis creates significant financial toxicities for patient and their families [25][26][27] , we found that participants were 3 times more likely to engage in diabetes-related CRN compared with cancer-related CRN. Participants who reported cancer-related CRN reported higher rates of delaying or forgoing not seeing an oncologist due to cost compared with other cancer-related CRN behaviors.…”
Section: Discussioncontrasting
confidence: 61%
“…Cancer remains the second most costly disease among Americans with a 27% rise in cost within the past 10 years [ 2 – 4 ]. The annual costs of cancer care are estimated to exceed $245 billion dollars by 2030 [ 5 – 7 ]. Delays in cancer detection can lead to decreased functional outcomes, productivity loss, treatment complications, reduced health-related quality of life, and increased healthcare costs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the Veterans Health Administration serving as America's largest integrated health clinic, providing Veterans with equal access to healthcare, many Veterans remain at risk of poorer outcomes from lung cancer due to multi-level barriers. These barriers include complex comorbidities, psychosocial concerns, poor social support, severe complications from social determinants of health such as food and housing insecurity [ 3 ], and limited transportation [ 4 ], that impact Veterans' ability to engage fully in their care after a diagnosis of cancer [ [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%